Gastroesophageal resuscitative occlusion of the aorta: Physiologic tolerance in a swine model of hemorrhagic shock. Issue 6 (December 2020) - Tiba, Mohamad H.; McCracken, Brendan M.; Colmenero, Carmen I.; Plott, Jeffery S.; Leander, Danielle C.; Greer, Nicholas L.; Wang, Stewart C.; Shih, Albert J.; Eliason, Jonathan L.; Ward, Kevin R.
Abstract : BACKGROUND: Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been shown to be effective for management of noncompressible torso hemorrhage. However, this technique requires arterial cannulation, which can be time-consuming and not amendable to placement in austere environments. We present a novel, less invasive aortic occlusion device and technique designated gastroesophageal resuscitative occlusion of the aorta (GROA). In this study, we aimed to characterize the physiological tolerance and hemodynamic effects of a prototype GROA device in a model of severe hemorrhagic shock and resuscitation and compare with REBOA. METHODS: Swine (N = 47) were surgically instrumented for data collection. A 35% controlled arterial hemorrhage was followed by randomizing animals to 30-minute, 60-minute, or 90-minute interventions of GROA, REBOA, or control. Following intervention, devices were deactivated, and animals received whole blood and crystalloid resuscitation. Animals were monitored for an additional 4 hours. RESULTS: All animals except one GROA 90-minute application survived the duration of their intervention periods. Survival through resuscitation phase in GROA, REBOA, and control groups was similar in the 30-minute and 60-minute groups. The 90-minute occlusion groups exhibited deleterious effects upon device deactivation and reperfusion with two GROA animals surviving and no REBOA animals surviving. Mean (SD) arterial pressure in GROA and REBOA animals increased across all groups to 98 (31.50) mm Hg and 122 (24.79) mm Hg, respectively, following intervention. Lactate was elevated across all GROA and REBOA groups relative to controls during intervention but cleared by 4 hours in the 30-minute and 60-minute groups. Postmortem histological examination of the gastric mucosa revealed mild to moderate inflammation across all GROA groups. CONCLUSION: In this study, the hemodynamic effects and physiological tolerance of GROA was similar to REBOA. The GROA device was capable of achieving high zone II full aortic occlusion and may be able to serve as an effective method of aortic impingement. Abstract : Supplemental digital content is available in the text.